2010
DOI: 10.1380/ejssnt.2010.388
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Photodetector Based on Porous Silicon

Abstract: Electrical and photoresponse properties of Al/porous silicon/crystalline Silicon/Al structure (Al/pSi/c-Si/Al) were investigated. Unoxidized porous Si layer was made on single crystalline p-Si using anodic etching in aqueous HF at a current density of 60 mA/cm 2 for 20 min etching time. The structure of porous layer was investigated using SEM and FTIR. The electrical properties of the Al/pSi/c-Si/Al junction were studied using dark I-V , illuminated I-V and C-V measurements. The rise time of the detector was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…Sz( ten point height) was 119.7 nm and roughness average was 17.2 nm.from previous data and our results (irregular and randomly distributed), we can understand why structure of porous heterojunction is always nonuniformly distributed and the difference over large area may be considerable . agreement with those reported earlier [12]. The current reaches a saturation value at higher bias voltage > −2 , the electric field is strong enough to separate any generated pair for certain incident power.…”
Section: Measurementsupporting
confidence: 92%
“…Sz( ten point height) was 119.7 nm and roughness average was 17.2 nm.from previous data and our results (irregular and randomly distributed), we can understand why structure of porous heterojunction is always nonuniformly distributed and the difference over large area may be considerable . agreement with those reported earlier [12]. The current reaches a saturation value at higher bias voltage > −2 , the electric field is strong enough to separate any generated pair for certain incident power.…”
Section: Measurementsupporting
confidence: 92%
“…The peaks are observed and located at (650, 700, 750 and 800) nm with sensitivities of (0.24, 0.38, 0.61 and 0.69) A/W for samples prepared at 15min and etching current (7, 9, 11, and 13) mA respectively. The high responsivity of photodetector is increasing from fact that the porous surface is in caparison photons also because the low concentration of surface recombination which make the surfaces very passivity in addition to the high reflectivity of PSi for light in the visible and near infrared regions is extremely low which agree with [19].…”
Section: Resultssupporting
confidence: 55%
“…Spectral distribution measurements of photoconductive signal revealed a shift of the maximum sensitivity towards visible region shorter wavelengths. It is observed that the presence of a PS layer on p-Si wafer causes a shift in this maximum peak to a higher energy and higher responsivity of the photodetector is the sum two terms the sensitivity of the FTO/PS Schottky contact and is the sensitivity of the PS/p-Si heterojunction as well as the reflectivity of porous Si for visible and near infrared regions is very low and that agree with [13]. Also, Alwan et al reported that the porosity of the porous silicon layer leads to hence improve the sensitivity of the formed junction between the crystalline silicon and the PS layer [14].…”
Section: Electrical Propertiessupporting
confidence: 68%